Eksplorasi Faktor Kepercayaan dan Kepuasan Konsumen terhadap Kosmetik Halal pada Shopee - Mega Dewi Sri Utami; Syauqi, Ubait; Faraby, Muhammad Ersya; Lusianah Dhewi Findartika (Syamilah Publishing, 2025)
The increasing demand for halal cosmetics is driven by growing consumer awareness of product safety, halal certification, and religious compliance. Shopee, as one of the largest e-commerce platforms in Indonesia, has become a major marketplace for consumers seeking information and purchasing halal cosmetic products. This study aims to explore the factors that influence consumer trust and satisfaction toward halal cosmetics on Shopee. Using a qualitative approach through a Systematic Literature Review (SLR), this research analyzed 10 selected articles published between 2020 and 2025 focusing on halal cosmetics, consumer behavior, trust, satisfaction, and online purchasing decisions. The analysis reveals that consumers perceive halal cosmetics as safer and more reliable due to their halal-thayyib attributes. Trust is shaped by the clarity of halal certification, transparent product information, seller credibility, and authentic user reviews. Meanwhile, satisfaction is influenced by product quality, label accuracy, pricing, and service performance such as delivery speed and seller responsiveness. The integration of trust and satisfaction plays a central role in strengthening purchase decisions and encouraging repeat purchases. These findings highlight the importance of accurate digital information, verified halal labels, and consistent seller performance in enhancing consumer confidence and satisfaction in purchasing halal cosmetics through Shopee.